Stevia sp. – a non-calorie sweet herb - Singh, Manvendra; Saharan, Vinod; Rajpurohit, Deepak (Indian Farming, 2018)
Stevia is an emerging crop which produce non-caloric herbal sweetener. Stevioside, the major sweetener present in leaf and stem tissues of Stevia. It is an alternate substitute of sugar. Stevia is high potential natural sweetening agent that highly nutritious, delicious and non-toxic. It is also used in food additives for enhancing the flavours without affecting the blood sugar level with great therapeutic values.